The Dynamic Phase Transition Modulation of Ion‐Liquid Gating VO2 Thin Film: Formation, Diffusion, and Recovery of Oxygen Vacancies. (22nd March 2016) - Chen, Shi; Wang, Xi jun; Fan, Lele; Liao, Guangming; Chen, Yuliang; Chu, Wangsheng; Song, Li; Jiang, Jun; Zou, Chongwen
Abstract : Electrolyte gating with ionic liquids (IL) on correlated vanadium dioxide (VO2 ) nanowires/beams is effective to modulate the metal‐insulator transition (MIT) behavior. While for macrosize VO2 film, the gating treatment shows different phase modulation process and the intrinsic mechanism is still not clear, though the oxygen‐vacancy diffusion channel is always adopted for the explanation. Herein, the dynamic phase modulation of electrolyte gated VO2 films is investigated and the oxygen vacancies formation, diffusion, and recovery at the IL/oxide interface are observed. As a relatively slow electrochemical reaction, the gating effect gradually permeates from surface to the inside of VO2 film, along with an unsynchronized changes of integral electric, optical, and structure properties. First‐principles‐based theoretical calculation reveals that the oxygen vacancies can not only cause the structural deformations in monoclinic VO2, but also account for the MIT transition by inducing polarization charges and thereby adjusting the d‐orbital occupancy. The findings not only clarify the oxygen vacancies statement of electrolyte gated VO2 film, but also can be extended to other ionic liquid/oxide systems for better understanding of the surface electrochemical stability and electronic properties modulation. Abstract : The oxygen vacancies in VO2 thin films, produced by electrolyte gating with ionic liquids, can be recovered gradually by just heating it in the air, as clearly observed from the in situ metal–insulator phase transition measurement.